THE FIRST TOUR OF THE JAPANESE KABUKI THEATER IN THE USSR - N. G. Kulinich (Гуманитарные и юридические исследования)
The article highlights the history of the organization and implementation of the first tour of the Japanese Kabuki theater in the Soviet Union on the basis of the sources of personal origin and periodicals. It describes the dificulties encountered by the organizers of the tour. The article analyzes various aspects of the stay of Japanese artists in the country of the Soviets. Special attention is paid to the perception of the Japanese theatrical art by Soviet theater audience.